PENGENDALIAN MODUL ROTARY HANDLING STATION BEBASIS SEQUENTIAL FUNCTION CHART (SFC) - Deli Budiantoro; Agus Halim; Soeharsono G (Jurnal Ilmiah Teknik Mesin POROS, 2014)
Abstract: The system used in this day and age has made progress in its operations. In industry itself many use automated systems that only require a small operator to run a tool because it saves time, and safety is guaranteed. In this time the tool discussed Handling Station Rotary pneumatic system uses motion to move this tool. So that the tool can be moved according to plan also required the "brains" to run this tool. Where the brain is a Program Logic Controller (PLC) to save a program that has been created in order to move the tool. Program created in this thesis using Sequential Function Chart (SFC) using Zelio Soft application. For components that are needed in this form of censorship tool as a reader, selonoid as air regulator to move from such a device.